Pengaruh Dissolved Organic Carbon (DOC) pada Efektivitas Perbaikan Tanah Gambut dengan Metode Calcite Precipitation - Pradyta Galuh Oktafiani; Heriansyah Putra; Sutoyo Sutoyo (Jurnal Aplikasi Teknik Sipil, 2022)
The problems that are generally found in land preparation for infrastructure developments are the characteristics of soils that have low bearing capacity, such as peat soils. Calcite precipitation is a soil improvement method that utilizes biochemical reactions with the final product being calcite. Peat soil has different characteristics from other soils, that it has high levels of Dissolved Organic Carbon (DOC). The amount of DOC present in peat soil significantly affects the specific gravity, liquid limit, density, and strength of the soil. Therefore, it is necessary to evaluate whether DOC in peat soil can affect the effectiveness of the calcite precipitation method. The research was conducted on soil with high organic content (95.35%) and soil with moderate organic content (73,51%). The research was carried out through five stages, namely soil properties, test-tube experiment, soil samples treatment, Unconfined Compressive Strength (UCS) test, and evaluating the soil pH. The results of this study obtained in the form of high organic content have an additional strength of 76.47%. Medium organic content soil has an additional strength of 137.50. Thus, DOC has an effect on increasing soil strength in the calcite precipitation method.